Use of Artificial Intelligence for Rice Crop Manager backend datasets in Odisha - Gakhar, Shalini; Jardinero, Benedict; Bharti, Preeti; Castillo, Rowena; Vila, Jerome; Sharma, Sheetal (2023)
The cultivation of rice (Oryzasativa) necessitates contemporary crop and soil management practices. Therefore, Rice Crop Manager (RCM), a web-based decision support tool has been developed to provide site specific nutrient recommendations in Odisha, India.